The role of lysosomal cysteine proteases in tumor progression - M. S. Korovin; V. V. Novitsky; O. S. Vasiliyeva (Бюллетень сибирской медицины, 2009)
Cysteine cathepsins have been known for a long time to play an important role in cancer progression. Here we summarize their impact to the hallmark processes of malignant growth such as cell proliferation, apoptosis, angiogenesis, invasion and metastasis. We discuss the molecular mechanisms where cysteine cathepsins are participating through the degradation of the extracellular matrix, initiation of the proteolytic cascade by activating serine proteases and urokinase plasminogen precursors. Moreover, in addition to the tumorigenic and pro-metastatic functions of lysosomal cysteine proteases in the cancer cells, cathepsins originating from cells of the tumour microenvironment has been shown to participate in the processes leading to the tumor progression and metastasis. Taken together, that data support the concept of cysteine cathepsins as promising molecular targets for cancer therapy.